PREDICTION OF ACADEMIC RESILIENCE IN ADOLESCENTS THROUGH ACADEMIC, SOCIAL AND EMOTIONAL SELF-EFFICACY AND GENDER - S. Sevgi Uygur; Esra Asici; Merve Kocer (Istraživanja u Pedagogiji, 2023)
This study aimed to investigate the predictive roles of gender and self-efficacy (academic, social, and emotional) on the academic resilience of adolescents. Participants consisted of 346 adolescents (227 girls and 119 boys). Data were collected through the Academic Resilience Scale, the Self-efficacy Scale for Children, and a demographic information form, and analyzed with an independent simple t test, Pearson correlation, and multiple linear regression analysis techniques. The results showed that male adolescents achieved higher scores in academic resilience, social self-efficacy, and emotional self-efficacy. Gender, academic self-efficacy, social self-efficacy, and emotional self-efficacy in sum accounted for 49% of the variance in academic resilience. All independent variables with the exception of gender (being male) were statistically significant predictors for academic resilience in adolescents. Increases in academic, social, and emotional self-efficacy were found to lead to enhanced academic resilience.